Metabolic alkalosis with multiple salt unbalance: an atypical onset of cystic fibrosis in a child - Dimitri Poddighe; Lucia Castelli; Elena Virginia Comi; Ilaria Brambilla; Paola Bruni (Hygeia Press di Corridori Marinella, 2017)
Dehydration with multiple salt abnormalities is frequently encountered in the paediatric emergency department, during acute illnesses complicated by loss of body fluids. Metabolic alkalosis is not a common finding in dehydrated children. The presence of unusual electrolyte unbalance, such as metabolic alkalosis, hyponatremia, hypochloremia and hypokalemia, without evidence of renal tubular defects, is named as pseudo-Bartter syndrome. It can occur in several clinical settings and, in infancy, it is described as a potential complication of cystic fibrosis. We report a case of pseudo-Bartter syndrome representing the onset of cystic fibrosis in childhood.